Ostrácodos dulceacuícolas de la Formación Yaguarí, Pérmico Superior, R.O. del Uruguay (Ameghiniana, 2014)
The Yaguarí Formation crops out in a large area in northeastern Uruguay. The San Diego Member, the lower section of the formation, yielded a bivalve fauna assigned to the "Pinzonella neotropica assemblage" from Brazil and Paraguay. It also furnished the ostracod fauna that is described herein. Two new species, Darwinula herbsti Diaz Saravia sp. nov. and Gutschickia? uruguayensis Díaz Saravia sp. nov. are erected while other specimens are assigned to Carbonita aff, C. inflata Jones and Kirkby. Both the sedimentary facies and the invertebrate fauna suggest a relatively restricted environment of fresh to oligohaline waters.